Problematic placebos in physical therapy trials. - Maddocks, M; Kerry, R; Turner, A; Howick, J (Wiley, 2016)
The placebo controlled, randomised controlled trial is widely recognised as the gold standard design for providing evidence in health care. Yet controversies surrounding placebos persist, which include issues regarding ethics, legality, mechanisms, and even whether there should be such a thing as placebo at all. Here, we intend to highlight some of the difficulties in the design and use of placebo controls within physical therapy trials. Unlike placebo tablets, which can be constructed simply by removing the active or‘characteristic’ingredient, physical therapy treatments are often more complex, with many active features that cannot be easily separated. Based on the challenges of isolating the characteristic feature(s) of treatments, we explore the problem with constructing placebos in trials of physical therapies, drawing on philosophy of science as a basis for defining what a placebo is and is not. After pointing out common problems, we outline potential solutions using alternative designs that allow trials to remain rigorous, while at the same time avoiding the pitfalls introduced when using inadequate placebos.